ALASAN NORWEGIA MENERIMA DELAPAN RIBU PENGUNGSI SURIAH DITENGAH KRISIS XENOPHOBIA Norway Reason Accepting Eight Thousands Syrian Refugees in The Midst Of Xenophobia Crisis - Abbie Anggara (HI 16 UMY 167, 2016)
Europe currently is facing the biggest immigration crisis since the World War 2 with the increasing number of Syrian refugee which comes to Europe continent. Such crisis brings out a new problem, xenophobia plague across the Europe, and reports that indicating verbal or physical abuses based on xenophobia are also raising. Those cases mostly associated with right wing group, and this become a phenomenon in Europe. Even some of European political party adopting this ideology and clearly shows anti-refugee attitude. Norway becomes one of those country which its government controlled by right wing party. However, Norway made a contradictive policy which allowing eight thousand refugees to enter Norway territory in following two years or until 2017. That policy contradict with what the right wing government expressed that seeks a stricter policy towards immigration. The cause of this policy can be traced back to strong influence given by the opposition party and even by the coalition partners parties of the government itself, also the demands from the mass to accept more refugees.